Sequential exercise in triathletes: Variations in GH and water loss - Galy, O.; Chamari, K.; Peyreigne, C.; Mercier, J.; Hue, O. (PLOS ONE, 2014)
Growth hormone (GH) may stimulate water loss during exercise by activating sweating. This study investigated GH secretion and water loss during sequential cycling and running, taking postural changes into account. The two exercise segments had similar durations and were performed at the same relative intensity to determine their respective contributions to water loss and the plasma volume variation noted in such trials. Eight elite triathletes first performed an incremental cycle test to assess maximal oxygen consumption. Then, the triathletes performed one of two trials in randomized order: constant submaximal cycling followed by treadmill running (C1-R2) or an inversed succession of running followed by cycling (R1-C2). Each segment of both trials was performed for 20 minutes at ~75% of maximal oxygen consumption. The second trial, reversing the segment order of the first trial, took place two weeks later. During cycling, the triathletes used their own bicycles equipped with a profiled handlebar. Blood sampling (for GH concentrations, plasma viscosity and plasma volume variation) was conducted at rest and after each segment while water loss was estimated from the post- and pre-measures. GH increases were significantly lower in R2 than C2 (72.2±50.1 vs. 164.0±157 ng.ml-1.min-1, respectively; P<0.05). Water loss was significantly lower after C1-R2 than R1-C2 (1105±163 and 1235±153 ml, respectively; P<0.05). Plasma volume variation was significantly negative in C1 and R1 (-6.15±2.0 and -3.16±5.0%, respectively; P<0.05), not significant in C2, and significantly positive for seven subjects in R2 (4.05±3.1%). We concluded that the lower GH increases in R2 may have contributed to the smaller reduction in plasma volume by reducing sweating. Moreover, this lower GH response could be explained by the postural change during the transition from cycling to running. We recommend to pay particular attention to their hydration status during R1 which could limit a potential dehydration during C2.